Analisis Risiko Pelanggaran Data Pribadi Pada Wacana Pengembangan Sistem Ai Analisis Big-Data Pemerintah Dalam Stranas-Ka - Ananta, Bintang Rafli; Rahmayani, Chanidia Ari; Sugiarto, Laga; Nugroho, Anastasya Adityawati; Assalamah, Shabrina (Fakultas Hukum Universitas Mulawarman, 2025)
ABSTRACT The armed conflict in Myanmar has escalated since the military coup in 2021. In this armed conflict, many civilian casualties have fallen and civilian facilities have been destroyed. This type of research is normative legal research with a descriptive prescriptive nature. This scientific article consists of three sub-discussions. First, this scientific article discusses international regulations governing the protection of Myanmar civilians when a non-international armed conflict is taking place. Second, it discusses gross human rights violations committed by the Military Junta against Myanmar civilians when in conflict with the Rebel Forces. Third, it discusses international mechanisms that can be carried out to resolve the conflict and protect Myanmar civilians. The results of this study state that the armed conflict between the Rebel Forces fighting against the military junta in Myanmar territory meets the elements of a Non-International Armed Conflict as stipulated by International Humanitarian Law. Since the 2021 military coup, there have been many gross human rights violations by the military junta, including attacks on demonstrators, torture, cutting off access to aid, and indiscriminate airstrikes. International mechanisms that can be used to resolve this problem include conducting diplomatic intervention and international community political resolution, implementing accountability for enforcing international legal instruments, and conducting humanitarian intervention and civil protection.